1989
DOI: 10.1063/1.100985
|View full text |Cite
|
Sign up to set email alerts
|

Interface properties of HgCdTe metal-insulator-semiconductor capacitors

Abstract: The conductance method has been used to measure the density of interface states of the ZnS/Hg0.775Cd0.225Te metal-insulator-semiconductor (MIS) system with three different HgCdTe surface treatments. It is found that the density of fast interface states increases from ∼1011 eV−1 cm−2 at the conduction-band minimum to ∼1013 eV−1 cm−2 near the valence-band maximum. In addition, the interface states located in the lower part of the band gap communicate with the valence band so efficiently that the effective band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 7 publications
3
19
0
Order By: Relevance
“…An important practical problem in the development of highly sensitive infrared detectors based on HgCdTe is the choice of an optimal passivation coating [1,3]. To characterize the passivation coating quality, the results of studying the electrophysical characteristics of metal-insulator-semiconductor structures (MIS structures) are usually used [4][5][6]. Properties of MIS structures based on graded-gap MBE n-Hg 1-х Cd х Te with double-layer low-temperature plasma-chemical insulator SiO 2 /Si 3 N 4 have been studied in detail [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…An important practical problem in the development of highly sensitive infrared detectors based on HgCdTe is the choice of an optimal passivation coating [1,3]. To characterize the passivation coating quality, the results of studying the electrophysical characteristics of metal-insulator-semiconductor structures (MIS structures) are usually used [4][5][6]. Properties of MIS structures based on graded-gap MBE n-Hg 1-х Cd х Te with double-layer low-temperature plasma-chemical insulator SiO 2 /Si 3 N 4 have been studied in detail [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The MIS structures with different dielectric coatings (SiO 2 /Si 3 N 4 and anodic oxide films grown using ammoniac or KOH sources) were studied to compare the effects of the dielectric and interface properties on the photoelectrical characteristics. Figure 2 shows the photo-emf for MIS HgCdTe/SiO 2 /Si 3 N 4 structures without (1) and with (2) a graded-band-gap layer and for HgCdTe/АОF structures with (3,5) and without (4, 6) a graded-band-gap layer. Curves 3 and 4 correspond to the MIS structures with an anodic oxide film produced using an ammoniac source, and curves 5 and 6 -using a KOH source.…”
mentioning
confidence: 99%
“…Interest in MIS structures based on graded-band-gap epitaxial HgCdTe is due to the necessity to passivate the surfaces of the HgCdTe photodiode arrays and to additional possibilities such graded-band-gap structures offer for developing monolithic detectors. A number of papers are concerned with studying the properties of MIS structures based on bulk HgCdTe [2][3][4][5]. However, the electrophysical and photoelectrical properties of MIS structures based on graded-band-gap epitaxial HgCdTe are still not understood though these structures must have a number of special features due to the presence of subsurface graded-band-gap layers and high resistance of the epitaxialfilm volume because of small film thickness (usually less than 10 μm).…”
mentioning
confidence: 99%
“…It has been reported that the effects of generation-recombination, diffusion, and tunneling should be considered in the analysis of narrow-gap HgCdTe MIS structures. 6 While all these effects are theoretically possible, they can be distinguished by their temperature dependence. Tunneling should have weak dependence on temperature associated mainly with temperature variations of the bandgap.…”
Section: Response To ''Comment On 'Electrical Properties Of Epitaxialmentioning
confidence: 99%